Penerapan Model Think Talk Write untuk Meningkatkan Hasil Belajar Matematika Siswa SD - Siti Zahra; Prissy Patrisia Gurning; Mutiara Lestari Aritonang; Alfred Kristian Gulo; Taruli Marito Silalahi (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this article review is to evaluate the effectiveness of using Think Talk Write (TTW) learning modeling to improve elementary school students' mathematics learning outcomes. The TTW model involves a structured process of thinking, speaking, and writing to help students understand mathematical concepts better. The study method used is library research, where the data sources obtained are reviewed through books, scientific articles, scientific journals and other relevant written information. Data collection techniques are carried out through library research, focusing on literature related to the application of the TTW model in mathematics learning. The data obtained are analyzed using descriptive methods, which include tracing, reviewing and verifying in order to determine conclusions. The study data produced shows that the application of the TTW model can improve students' understanding and mathematical skills, and provide a clear picture of the effectiveness of this model in the context of mathematics education in elementary schools.